Ferrostatin-1 improves acute sepsis-induced cardiomyopathy via inhibiting neutrophil infiltration through impaired chemokine axis - Li, Jialin; Xiao, Fang; Lin, Bingsen; Huang, Zhilei; Wu, Mingyue; Ma, Huan; Dou, Ruoxu; Song, Xiaodong; Wang, Zhongxing; Cai, Changjie; Guan, Xiangdong; Xu, Jie; et al. (Frontiers in Cell and Developmental Biology, 2024)
IntroductionSepsis-induced cardiomyopathy is a common complication of sepsis and is associated with higher mortality. To date, effective diagnostic and management strategies are still lacking. Recent studies suggest that ferroptosis plays a critical role in sepsis-induced cardiomyopathy and ferroptosis inhibitor Ferrostatin-1 (Fer-1) improved cardiac dysfunction and survival in lipopolysaccharide (LPS) induced endotoxemia. However, the effects of Fer-1 in cardiac dysfunction in the early stages of cecal ligation and puncture (CLP) induced sepsis remains unclear. Our study aims to elucidate the role of Fer-1 in the acute phase of peritonitis sepsis induced cardiac injury.Methods and ResultsCLP was used to induce peritonitis sepsis in mice. Pretreatment of ferroptosis inhibitor ferrostatin-1 (Fer-1) was used in the in vivo models. Survival was monitored for 48h. Cardiac function and histology were analyzed 6h after surgery. We found that ejection fraction (EF) remained normal at 6h after CLP, but the contractility detected by cardiac muscle strain analysis was significantly reduced, along with increased immune cell infiltration. Pretreating the CLP mice with 5 mg/kg Fer-1 significantly reduced mortality. At 6h after CLP, ferroptosis key regulator Gpx4, cardiac iron and malonaldehyde (MDA) did not change, but ferroptosis marker gene expression increased. Fer-1 treatment showed beneficial effects in cardiac function, less myocardial inflammatory cytokine expression and significantly inhibited immune cells, especially neutrophil infiltration in the heart. Consistently, expression of neutrophil associated chemokines (Ccrl2, Cxcl2, Cxcl3 and Cxcl5) as well as extracellular matrix (ECM) degradation enzymes (Adamts1, Adamts4, Adamts9 and Mmp8) significantly decreased in Fer-1 pre-treated CLP heart.Conclusion and DiscussionOur findings suggest that Fer-1 inhibits neutrophil infiltration in early sepsis by disrupting the chemokine axis, highlighting its potential as a therapeutic option to manage acute immune overactivation in early stages of sepsis-induced cardiomyopathy.